Penyelesaian Vehicle Routing Problem Untuk Efisiensi Rute Pendistribusian Produk Minuman Teh Pucuk Harum Menggunakan metode Saving Matriks Studi Kasus (PT. Cipta Niaga Semesta Palu) - Putrafi, R; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2020)
Vehicle Routing Problem Is a Problem related to the route of product distribution to the consumers. With the existence of these problems a company is expected to seek away a way so that the distribution process can arrive on time to scattered consumers and obtain more efficient routes and costs. Therefore a method which can help the process of scheduling a good route and obtaining optimum costs and efficient delivery was used. One of the methods used was Saving Matrix, which in its operation could efficient the delivery route so that the minimum total distance was obtained. The company's actual mileage was greater than the distance travelled by the route after using the Saving Matrix method. The total difference in distance produced was 106,35 km or more saving 41,2 % from the actual distance of the company and using Saving Matrix could save the distribution costs of Rp. 5.687.640 or save 33,8 % of the cost before applying the method.